ESTIMATING THE INDIVIDUAL DEMAND FUNCTION FOR TABLE EGGS IN IRAQ USING THE ARDL MODEL FOR THE PERIOD 2003-2023 - Hasan, Noor Eidan; Ali , Suaad Hussein (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study aimed to estimate and analyze the individual demand function for table eggs in Iraq for the period (2003-2023) and calculated the demand elasticity as they determine the relative relationship between price and quantity. The research was based on the frontier approach cointegrationusing the ARDL model in estimating the consumer demand function. As a result of both short-ran and long-ran demand elasticity showed , we conclude that eggs are a natural and very necessary commodity for the Iraqi consumer as they cannot be dispensed with even if their prices rise, the consumer will work to reduce a small part of them, and this is what the price elasticity of demand showed (-0.56, -0.73). As for the income elasticity, it showed that it is a commodity with superior goods for the consumer's income in the short and long ran as follows (1.58, 1.36) respectively, meaning that it is a commodity elastic to changes in income because the elasticity coefficient is greater than 1%. Based on what has been concluded, the researcher can recommend working to support egg production projects and working to achieve self-sufficiency in it, as it is a necessary and important commodity for the consumer, and that increasing local production works to increase the supply of eggs so that they are available at appropriate prices that the consumer can buy it.